The economics and politics of regulation : a behavioral approach - Needham, Douglas; douglas needham (Boston : Little, Brown, 1983)
The author adopts a broad behavioral approach, focusing on the determinants of people's perceptions and evaluations of regulation's effects. The book is intended to serve the needs of upper-level undergraduate and introductory graduate courses dealing with government regulation of business in colleges and universities, business schools, and law schools.
Includes index.
Bibliography: p. 447-475.
oo 24/09/2018
Loans
Keywords: a behavioral approach; Industrial policy; Trade regulation; United States